HATCHING PERFORMANCE OF ARBOR ACRES BROILER BREEDER STRAIN AT FOUR PRODUCTION PHASES WITH THREE EGG WEIGHTS AND STORAGE - H. M. Ishaq; M. Akram; M. E. Baber; A. W. Sahota; A. S. Jatoi; R. Yousaf; F. Hussnain; R. Naeem (Journal of Animal and Plant Sciences, 2018)
The present study was conducted to evaluate the hatching performance (average egg size, moisture loss, fertility, hatchability and hatch of fertile eggs) in Arbor Acre broiler breeder strain eggs during four production phases th (pre-peak, 25-28; peak, 29-36; post-peak, 37-52 and terminal, 53-56 weeks of age), categorized into three egg weights (small, medium and large; changed in each production phase), maintained at three different storage periods (1, 4 and 7- days) and replicated 6 times. A total of 93312 fertile eggs (pre-peak: 11664, peak: 23328, post-peak: 46656 and terminal: 11664) in 4 production phases were subjected to hatching in a commercial hatchery. The data were analyzed using ANOVA technique under randomized complete block design in a 4×3×3 factorial arrangement and means were compared using DMR Test. Results showed significant (pd0.05) differences for average egg size and fertility percent in large egg weight category alone as well as its interaction with all three storage periods. Significantly ( pd0.05) higher moisture loss was observed in large and small egg categories and highest in seven days storage alone and its interaction with all egg weight categories during post-peak. Regarding hatching traits, significantly (Pd0.05) highest hatchability percent and hatch of fertile percent were observed in large egg weight category alone and in interaction between egg weight categories and storage periods during pre-peak and peak, while during post-peak and terminal phases medium egg weight category showed higher hatchability and hatch of fertile percent. Significantly (pd0.05) higher hatchability and hatch of fertile percent were observed in one and four day storage period. It is concluded from the present study that large egg weight category coupled with 1 or 4 day storage period had maximum fertility, hatchability and hatch of fertile percent in Arbor Acre broiler breeder strain.
Keywords: Broiler breeder strain; egg size; fertility and hatchability percent; hatch of fertile; production phases.